Resistance welding pocket handbook (American Welding Society, 2011)
General information relating to the operation of common resistance welding equipment.
"AWS RWPH:2011."
Keywords: Electric welding -- Handbooks, manuals, etc.; Electric welding -- Equipment and supplies.; elektronické knihy; electronic books